Ionic Rigid Organic Dual-State Emission Compound With Rod-Shaped and Conjugated Structure for Sensitive Al3+ Detection - Lv, Hongying; Wei, Lingzhong; Guo, Song; Zhang, Xiaofeng; Chen, Feixia; Qin, Xiaojin; Wei, Chun; Jiang, Bingli; Gong, Yongyang (Frontiers in Chemistry, 2022)
Dual state emission (DSE) luminogens, a type of luminescent materials which can effectively emit light in both dilute solution state and solid state, have attracted tremendous attentions, due to the widespread applications in chemical sensing, biological imaging, organic electronic devices, and so on. They overcome the shortcomings of aggregation-induced emission (AIE)-type compounds that do not emit light in dilute solutions and aggregation-induced quenching (ACQ)-type compounds that do not emit light in concentrated or aggregated state. This work reports a novel ionic DSE material based on rigid rod-shaped organic conjugated structure using 4,4'-bis(2-sulfonatostyryl) biphenyl disodium salt (BSBDS), the ion repulsion effect can reduce the strong - interaction in aggregation and achieve high-efficiency luminescence in solution and solid states. In addition to the excellent DSE characteristics, BSBDS also exhibits mechanochromic nature and sensitive detection performance for aluminum ion (Al3+).